Gel breaker for well cementation as well as preparation method and application of gel breaker
By using chitosan and sodium dodecyl sulfate to construct a film-coated debonding agent wrapped in ammonium persulfate or potassium persulfate, the problems of low efficiency and environmental hazards in cementing are solved, and rapid debonding and protection are achieved Reservoir and cost-reducing effects.
Patent Information
- Application Number
- CN202411723838.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing glue breakers have problems such as rapid reduction of the viscosity of fracturing fluid, weakening of sand carrying capacity, increasing filtrate, early desanding and formation pollution in the cementing work, especially in high-temperature and high-salt environments, and traditional Delay-release degreasing agents are inefficient, potentially harmful to the environment and are costly.
Using a cracking agent composed of chitosan, sodium dodecyl sulfate, acrylic acid, liquid paraffin, anhydrous ethanol, ammonium persulfate or potassium persulfate, the film-coated structure is constructed through wrapping technology, and the oxidizing agent is used to make the static attraction effect. Quick release in the gel to achieve rapid glue breaking.
This rubber breaker can efficiently break glue in a short time, protect the reservoir, improve the production efficiency of oil and gas wells, reduce development costs, and is environmentally friendly and suitable for complex formation conditions.
Smart Images

Figure CN119220235A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of oilfield chemical cementing work and relates to a cementing breaker and a preparation method and application thereof. Background Art
[0002] In the development of oil and gas fields, in order to effectively control downhole pressure, improve cementing quality and prevent formation water breakthrough, HPAM (partially hydrolyzed polyacrylamide) type gels are often used for temporary plugging. This substance is widely used in cementing, fracturing and other production stimulation operations due to its excellent viscoelasticity and adjustable viscosity. However, if the gel is not broken in time, it may block the pores and cracks of the oil and gas layer, affect the flow of oil and gas, thereby reducing the production efficiency of the oil and gas wells and affecting the long-term production potential of the reservoir. If the gel is not broken in time, it may block the pores and cracks of the oil and gas layer, affect the flow of oil and gas, reduce the production efficiency of the oil and gas wells, and damage the long-term production potential of the reservoir. Attention should be paid when cementing to ensure long-term stable production of oil and gas wells. Therefore, once these gels have completed their plugging task, they must be quickly and thoroughly destroyed.
[0003] Oxidizing breakers such as potassium persulfate and ammonium persulfate are commonly used breakers. However, in cementing work, if they are directly added to the pre-fluid, the viscosity of the fracturing fluid will drop rapidly, the sand carrying capacity will be weakened, and the filtrate will increase, affecting the fracture-making ability of the fracturing fluid during construction, and even causing premature sand removal, leading to construction failure. Moreover, oxidizing breakers are non-specific reactants and can react with any reactants encountered, such as pipes, formation matrix and hydrocarbons, to generate pollutants that are incompatible with the formation, causing formation damage.
[0004] Delayed-release breakers can effectively avoid the above problems and provide more effective breaking effects. However, existing delayed-release breakers generally have some defects, such as long breaking time, low efficiency, potential harm to the environment, and relatively high cost. Especially under complex formation conditions, such as high temperature and high salt environment, the effect of traditional breakers is often greatly reduced and it is difficult to meet industrial needs.
[0005] Therefore, it is particularly important to develop a breaker that can efficiently break the gel in a short time and is environmentally friendly and cost-effective. Summary of the invention
[0006] The main purpose of the present invention is to develop a cementing breaker, preparation method and application for leaky reservoirs. The breaker is added to the gel during the construction process to quickly break the gel, which plays an important role in reservoir protection and plugging removal.
[0007] During the construction process, it is added to the pre-fluid system to quickly break the gel in the target layer, which plays an important role in reservoir protection and plugging removal.
[0008] The cementing breaker of the present invention comprises, by weight percentage, 2-3 parts of chitosan, 2 parts of sodium lauryl sulfate, 1 part of acrylic acid, 1 part of liquid paraffin, 1 part of anhydrous ethanol, 2 parts of oxidant and 120 parts of water.
[0009] The oxidant is ammonium persulfate or a mixture of ammonium persulfate and potassium persulfate. When a mixture of ammonium persulfate and potassium persulfate is used, the mass ratio of ammonium persulfate to potassium persulfate is 1:1.
[0010] The preparation method of the cementing breaker comprises the following specific steps: (1) Weigh the raw materials according to the proportion; (2) adding acrylic acid and anhydrous ethanol into water and stirring at a uniform speed, then adding chitosan, stirring evenly, and then adding liquid paraffin to obtain slurry I; (3) adding sodium dodecyl sulfate to water, stirring evenly, and then adding an oxidant to obtain slurry II; (4) Drop slurry I into slurry II to obtain a degumming agent.
[0011] The degumming agent obtained by the invention is spherical, with a diameter of millimeter level, and a film coating is constructed with sodium dodecyl sulfate and chitosan, and the inside is wrapped with ammonium persulfate solution or a solution of ammonium persulfate and potassium persulfate.
[0012] The stirring speed in steps (2) and (3) is 550 r / min. -1 Slurry I is dripped into slurry II at a rate of one drop every three seconds, otherwise the number of broken balls will exceed 50% or no balls will be formed.
[0013] In the present invention, a mixed adsorption layer and a multilayer interface film are formed between chitosan molecules and sodium dodecyl sulfate molecules to enhance interfacial activity. Chitosan is a rich cationic biopolyelectrolyte, which is compounded with sodium dodecyl sulfate, and the electrostatic attraction force is used to enhance the bonding between chitosan and sodium dodecyl sulfate molecules to construct a film coating structure, so that it can carry an ammonium persulfate solution or an ammonium persulfate and potassium persulfate solution carrier. The carrier is liquid, which can play a faster degelling effect. In the present invention, acrylic acid and anhydrous ethanol help chitosan to be better soluble in water.
[0014] Chitosan, also known as deacetylated chitosan, is a widely-existing natural polymer material known for its hard molecular structure and wide range of applications. The charge density of this material can be controlled by adjusting the degree of deacetylation and pH. Changes in pH affect the protonation state of chitosan molecules, thereby changing the flexibility of the molecular chain and the interaction between molecules, which has an important influence on the stability of the emulsion formed by it. Therefore, chitosan exhibits obvious pH-responsive characteristics and shows great potential in the research of stimulus-responsive materials. However, due to the small number of hydrophobic groups in chitosan molecules and the spatial barriers generated by the random distribution of these groups, its contact ability with the oil-water interface is weakened. The combination of surfactants and chitosan can enhance the strength of the interfacial film and reduce the aggregation between droplets, thereby improving the stability of the emulsion and its temperature and salt resistance.
[0015] The debonding agent of the present invention is added into the cementing pre-fluid system to play a debonding role. When used, the pre-fluid system with the debonding agent is directly pumped into the position blocked by the HPAM gel to achieve the purpose of rapid deblocking.
[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The breaker described in the present invention uses a wrapping technology to wrap the oxidant and is used in conjunction with a cementing pre-fluid. Unlike conventional direct injection breakers, the carrier core can be controlled to achieve precise release after reaching the target formation.
[0017] (2) The debonding agent of the present invention quickly debonds the HPAM gel originally solidified in the formation, so that after adding it into the pre-fluid system, it can effectively plug the lost reservoir when reaching the target layer, laying the foundation for subsequent cementing work.
[0018] (3) The preparation method of the debonding agent of the present invention is simple, reliable, and easy to mass produce and apply on site. It can not only improve the development efficiency of oil and gas fields, but also help reduce development costs and protect the environment. It has important practical value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The breaker obtained in Example 1; Figure 2 It is a breaker after releasing the carrier core; Figure 3 The breaker obtained in Example 5; Figure 4 It is the viscosity change curve under different breaker dosage; Figure 5 The breaker obtained in Comparative Example 1; Figure 6 This is the degumming agent obtained in Comparative Example 2. DETAILED DESCRIPTION
[0020] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0021] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this document, it indicates the presence of features, steps, operations and / or combinations thereof.
[0022] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0023] Example 1 The cementing debonding agent comprises the following raw materials, in parts by weight: 2 parts of chitosan, 2 parts of sodium lauryl sulfate, 1 part of acrylic acid, 1 part of liquid paraffin, 1 part of anhydrous ethanol, 1 part of ammonium persulfate, 1 part of potassium persulfate, and 120 parts of water.
[0024] The preparation steps are: (1-1) Weigh the raw materials in proportion and set aside; (1-2) Add 1 part of acrylic acid and 1 part of anhydrous ethanol to 80 parts of water and stir evenly. Then add 2 parts of chitosan and stir at 550 r / min. -1 Stir at a high speed for 30 minutes, add 1 part of liquid paraffin and continue stirring for 1 minute to obtain slurry I; (1-3) Add 2 parts of sodium dodecyl sulfate to 40 parts of water and stir evenly. Then add 1 part of ammonium persulfate and 1 part of potassium persulfate. Stir at a speed of 550 r / min. -1 , to obtain slurry II; (1-4) Place slurry I in a separatory funnel and drip into slurry II at a rate of one drop every three seconds to obtain a core-carrying transparent ball, i.e., a gel breaker, such as Figure 1 shown.
[0025] Example 2 The weak acid environment of the pre-pad system was simulated (the formula of the pre-pad system was: 100g water + 8% HPAM aqueous solution + 0.1g sodium dodecyl sulfate + 0.1g Jiahua G grade cement). The breaker prepared in Example 1 was placed in the pre-pad system. It can be observed that the breaker automatically releases the carrier core. After the carrier core is released, Figure 2 shown.
[0026] Example 3 Chitosan, sodium dodecyl sulfate (SDS) and liquid paraffin were prepared in different ratios, and a breaker was prepared according to the synthesis method of Example 1. The prepared breaker was placed in the weakly acidic pre-liquid described in Example 2 to form a mixed slurry III. The titration method was used to detect whether the carrier contained ammonium persulfate and potassium persulfate.
[0027] Using the oxidizing properties of ammonium persulfate and potassium persulfate, titration is performed with reducing agent potassium iodide and starch solution. The specific steps are: add potassium iodide and water to the mixed slurry III, shake well and place in the dark for a certain period of time, at which time the solution turns blue, then titrate with sodium thiosulfate standard titration solution, and it can be observed that the blue color of the solution disappears. The complete disappearance of the blue color is recorded as the release time, as shown in the following table: .
[0028] Example 4 The preparation steps of HPAM type gel are: The gel that can reach the target layer and seal the target layer is composed of the following raw materials by weight: 2 parts of HPAM, 1 part of organic chromium cross-linking agent, 1 part of stabilizer, and 20 parts of distilled water; (1-1) Weigh the raw materials in proportion and set aside; (1-2) Add 2 parts of HPAM to 20 parts of distilled water and stir evenly at a stirring speed of 550 r·min -1 , obtain slurry IV; (1-3) Mix 1 part of stabilizer with slurry IV and stir evenly at a stirring speed of 550 r / min. -1 , obtain slurry V; (1-4) Mix slurry V with 1 part of organic chromium crosslinking agent to form a homogeneous slurry, and stir evenly at a stirring speed of 550 r·min -1 , placed in a heating furnace at 80°C for 6 hours, adjusted the pH, and obtained gel G1.
[0029] Example 5 The cementing debonding agent comprises, by weight percentage, 2 parts of chitosan, 2 parts of sodium lauryl sulfate, 1 part of acrylic acid, 1 part of anhydrous ethanol, 1 part of liquid paraffin, 2 parts of ammonium persulfate and 120 parts of water.
[0030] The preparation steps are: (1-1) Weigh the raw materials in proportion and set aside; (1-2) Add 1 part of acrylic acid and 1 part of anhydrous ethanol to 80 parts of water and stir evenly. Then add 2 parts of chitosan and stir at 550 r / min. -1Stir at a high speed for 30 minutes, add 1 portion of liquid paraffin and continue stirring for 1 minute to obtain slurry VI; (1-3) Add 2 parts of sodium dodecyl sulfate to 40 parts of water and stir evenly, then add 2 parts of ammonium persulfate at a stirring speed of 550 r·min -1 , to obtain slurry VII; (1-5) Place slurry VI in a separatory funnel and drip into slurry VII at a rate of one drop every three seconds to obtain a transparent spherical breaker, such as Figure 3 shown.
[0031] Example 6 To simulate the pre-liquid system, the HPAM gel prepared in Example 4 was mixed with the breaker prepared in Example 1 at a ratio of 1:10 (mass ratio) and 1:15 (mass ratio), and with the breaker prepared in Example 5 at a ratio of 1:10 (mass ratio). After adding the pre-liquid system, the mixture was stirred evenly at a stirring speed of 550 r·min. -1 , set the gel breaking temperature environment to 80℃, observe the gel breaking situation by testing the viscosity change, and record the gel breaking time respectively. The specific results are as follows: This time, a rotational viscometer is used to test the viscosity of the liquid. The viscosity value is calculated by using the resistance encountered by the rotating column when it rotates in the liquid. The calculation formula of the rotational viscometer is: ; in, N is the rotation speed of the spin column (rpm), R is the radius of the rotating cylinder (mm), V is the speed of the liquid flowing on the rotating column (mm / s), and the unit of viscosity is cP (centipoise). The viscosity value calculated by the rotational viscometer can be used to determine the flow properties and quality of the liquid. The viscosity change curve is shown in Figure 4 shown.
[0032] Comparative Example 1 A degumming agent comprises the following raw materials, measured in percentage by weight: 2 parts of chitosan, 1 part of anhydrous ethanol, 1 part of liquid paraffin, 1 part of acrylic acid, 2 parts of ammonium persulfate and 120 parts of water.
[0033] The preparation steps are: (1-1) Weigh the raw materials in proportion and set aside; (1-2) Add 1 part of acrylic acid and 1 part of anhydrous ethanol to 80 parts of water and stir evenly. Then add 2 parts of chitosan and stir at 550 r / min. -1 Stir at a high speed for 30 minutes, add 1 portion of liquid paraffin and continue stirring for 1 minute after stirring evenly to obtain slurry VIII; (1-3) Add 2 parts of ammonium persulfate to 40 parts of water and stir evenly at a stirring speed of 550 r·min -1 , to obtain slurry IX; (1-4) Place slurry VIII in a separatory funnel and drip into slurry IX at a rate of one drop every three seconds to obtain a mixed slurry. Encapsulation cannot be achieved, such as Figure 5 shown.
[0034] Comparative Example 2 A degumming agent comprises the following raw materials, measured by weight percentage: 2 parts of chitosan, 2 parts of anionic surfactant salt-type fatty alcohol ether carboxylate, 1 part of anhydrous ethanol, 1 part of liquid paraffin, 1 part of acrylic acid, 1 part of ammonium persulfate, 1 part of potassium persulfate and 120 parts of water.
[0035] The preparation steps are: (1-1) Weigh the raw materials in proportion and set aside; (1-2) Add 1 part of acrylic acid and 1 part of anhydrous ethanol to 80 parts of water and stir evenly. Then add 2 parts of chitosan and stir at 550 r / min. -1 Stir at a high speed for 30 minutes, add 1 portion of liquid paraffin and continue stirring for 1 minute after stirring evenly to obtain slurry X; (1-3) Add 2 parts of anionic surfactant salt-type fatty alcohol ether carboxylate to 40 parts of water and stir evenly. Then add 1 part of ammonium persulfate and 1 part of potassium persulfate. Stir at a speed of 550 r·min. -1 , obtain slurry XI; (1-4) Place slurry X in a separatory funnel and drip into slurry XI at a rate of one drop every three seconds to obtain a mixed hard plastic material. Spherical encapsulation cannot be achieved, such as Figure 6 shown.
[0036] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A gel breaker for cementing, characterized in that: The raw material composition is as follows by weight percentage: 2-3 parts of chitosan, 2 parts of sodium lauryl sulfate, 1 part of acrylic acid, 1 part of liquid paraffin, 1 part of anhydrous ethanol, 2 parts of oxidant and 120 parts of water.
2. The cementing breaker according to claim 1, characterized in that: The oxidant is ammonium persulfate or a mixture of ammonium persulfate and potassium persulfate.
3. The cementing breaker according to claim 2, characterized in that: In terms of mass ratio, ammonium persulfate: potassium persulfate = 1:
1.
4. The method for preparing a cementing breaker according to any one of claims 1 to 3, characterized in that: The specific steps are: (1) Weigh the raw materials according to the proportion; (2) adding acrylic acid and anhydrous ethanol into water and stirring at a uniform speed, then adding chitosan, stirring evenly, and then adding liquid paraffin to obtain slurry I; (3) adding sodium dodecyl sulfate to water, stirring evenly, and then adding an oxidant to obtain slurry II; (4) Drop slurry I into slurry II to obtain a degumming agent.
5. The method for preparing a cementing breaker according to claim 4, characterized in that: The stirring speed in steps (2) and (3) is 550 r / min. -1 .
6. The method for preparing a cementing breaker according to claim 4, characterized in that: Slurry I was dripped into slurry II at a rate of one drop every three seconds.
7. Use of the cementing breaker according to any one of claims 1 to 3 in a cementing pre-fluid system.
Citation Information
Patent Citations
Efficient microcapsule gel breaker and preparation method thereof
CN102627958A
Gel breaker microcapsule controlled to release concentratedly in 2-3 h and preparation method thereof
CN102627959A
Chitosan microalgae oil slow-release microcapsules and preparation method thereof
CN105078927A
Novel clean fracturing liquid and preparation method thereof
CN107236532A
PH-responsive oil-displacing agent composition, oil-displacing agent, and preparation method and application thereof
CN112480895A
